Coulomb interaction and spin-orbit coupling calculations of thermoelectric properties of the quaternary chalcogenides Tl2PbXY4 (X = Zr, Hf and Y = S, Se). (1st September 2015) - Azam, Sikander; Khan, Saleem Ayaz; Minar, Jan; Khan, Wilayat; Ud Din, Haleem; Khenata, R; Murtaza, G; Bin-Omran, S; Goumri-Said, Souraya
Abstract: The increase in energy demands is leading to growing interest in new thermoelectric inorganic materials, such as the chalcogenides. The recently synthesized quaternary chalcogenide, Tl2 PbXY4 (X = Zr, Hf and Y = S, Se), compounds were investigated using the full potential linear augmented plane wave method based on density functional theory. We used the generalized gradient approximation plus the optimized effective Hubbard parameter U to treat the exchange correlation. The existence of heavy metals (Tl, Pb and Hf) required the application of relativistic spin–orbit coupling via a second variational procedure. Tl2 PbHfS4, Tl2 PbHfSe4, Tl2 PbZrS4 and Tl2 PbZrSe4 compounds were found to be semiconductors with indirect band gaps of 0.911, 0.659, 0.983 and 0.529 eV, respectively. The types of carriers and electrical transport properties of Tl2 PbXY4 (X = Zr, Hf and Y = S, Se) are attributed to the Tl-d and S/Se-s electronic states near the Fermi level. Optical properties were investigated via the calculation of dielectric function and reflectivity. Using Boltzmann theory, we compared the thermoelectric properties and we found that Tl2 PbHfS4 could be a good candidate for thermoelectric devices.